Impact of altitude correction on bronchopulmonary dysplasia prevalence: A systematic review and meta-analysis - Madina Syzdykova; Marina Morenko; Kseniya Shnaider; Saltanat Urazova; Ulbossyn Saltabayeva; Nelli Bugayeva; Zhuldyzay Kagenova (PLoS ONE, 2025)
Bronchopulmonary dysplasia (BPD) presents a significant respiratory challenge in infants born prematurely. Socioeconomic factors and environmental determinants, including altitude, play pivotal roles in shaping respiratory health outcomes among premature infants. This study aimed to investigate the prevalence of BPD among preterm infants based on altitude, considering the impact of altitude correction on prevalence estimates. By examining altitude-related variations in BPD prevalence, the study sought to provide insights essential for guiding interventions aimed at preventing and managing respiratory conditions in this vulnerable population. The study protocol was registered with PROSPERO, and a systematic search of five databases (PubMed, Web of Science, ScienceDirect, ProQuest, and Google Scholar) was conducted without any restrictions on the date of publication. Eligible studies were identified based on predefined inclusion criteria, including retrospective or prospective studies reporting BPD prevalence at different altitudes, the use of standard diagnostic criteria for BPD, and the exclusion of studies involving non-human subjects or those lacking altitude-adjusted data. The risk of bias assessment was conducted using the Critical Appraisal Skills Programme checklist. Statistical analysis included calculating pooled prevalence estimates using a random-effects model, performing subgroup analyses, and assessing heterogeneity and publication bias. The search yielded 339 records, of which ten articles met the inclusion criteria and had a low risk of bias. The altitude-unadjusted BPD prevalence was 41.35% (95% CI 28.62; 55.34%) and ranged from 19.73% (95% CI 16.44; 23.48%) to 71.02% (95% CI 68.33; 73.56%) across different altitude categories. The altitude-adjusted pooled mean BPD prevalence was 26.70% (95% CI 19.60; 35.25%). This systematic review and meta-analysis highlight altitude-related variations in BPD prevalence among preterm infants. Altitude adjustment is crucial for understanding the true prevalence of BPD and guiding tailored interventions in high-altitude regions.